Der Stadt-Land-Gegensatz in der europäischen Geschichte des 19. und 20. Jahrhunderts –: ein Abriss - Lenger, Friedrich (Comparativ, 2008)
The relationship between city and country in 19th and 20th century Europe – a brief sketch While authors like Marx attached prime importance to the relationship between the city and the country many sociologists today deny that there are any meaningful distinctions left between them. The article tries to sketch the most important changes and the most important regional variations within Europe over the last two hundred years and in doing so gives special prominence to structural changes within the economy and society. Without wanting to diminish the importance of processes of industrialization for the dissolution of earlier dividing lines between the (walled) city and its surroundings the articles proposes to make use of recent work on the economics of agglomeration because such an approach has at least two advantages: It allows to identify more clearly the exceptional character of industrial towns in coal regions and to conceptualize more convincingly the conditions of growth of the many other types of cities growing rapidly in the late 19th and 20th century. This is especially true for the cities of Southern Europe where the long and widespread absence of industrialization did not prevent urban growth. Well into the 21st century the relationship between the city and the country in these regions nevertheless shows quite different features than the metropolitan regions in the northwestern parts of the continent. (The exclusion of Eastern Europe is solely due to the fact that another contribution to this volume deals with it.)